2020
DOI: 10.3390/bs10080128
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Post-Stroke Pain and The Impact on Quality of Life: An Integrative Review

Abstract: Background: Many people experience post-stroke pain (PSP). It is a long-term consequence of stroke that commonly goes unrecognised and untreated. As a result, an integrative review is needed to identify the primary factors that affect PSP and determine the impact on quality of life (QOL). Methods: An integrative review using a quantitatively led data synthesis, supported by qualitative evidence, was conducted. Results: Fourteen studies were identified and 2415 (968 females, 1447 males) people were included. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 59 publications
0
13
0
Order By: Relevance
“…Although previous studies show that post-stroke pain affects around 40% of stroke survivors [27] we are not aware of studies of post-stroke pain during the COVID-19 pandemic. We identified that during the pandemic pain interference and intensity was significantly higher compared those seen pre-pandemic.…”
Section: Discussionmentioning
confidence: 89%
“…Although previous studies show that post-stroke pain affects around 40% of stroke survivors [27] we are not aware of studies of post-stroke pain during the COVID-19 pandemic. We identified that during the pandemic pain interference and intensity was significantly higher compared those seen pre-pandemic.…”
Section: Discussionmentioning
confidence: 89%
“…Stroke is a leading cause of disability worldwide, resulting in 1 or more physical and/or cognitive impairments, 1 , 2 , 3 , 4 , 5 which are often accommodated by sensory, perceptual, emotional, and social conditions that may affect quality of life. 6 , 7 , 8 Regular exercise has been recognized as a critical behavior for chronic disease prevention and overall health improvement in the general population. 9 , 10 For people poststroke, exercise can also be beneficial, with evidence demonstrating its positive effects on physical function, 11 cognition, 12 and quality of life.…”
mentioning
confidence: 99%
“…Chronic pain is a common symptom in post-stroke patients increasing patients’ disability and affecting rehabilitation outcomes. To date, the management of these patients is a challenge in the neurorehabilitation setting [ 67 ]. As a matter of fact, it is important to deeply understand all the factors involved in pain occurrence and chronification as well as its impact on disability and HrQoL.…”
Section: Discussionmentioning
confidence: 99%